Comparison of time taken to obtain an arterial blood gas result at the bedside using the ProximaTM point of care machine vs. a standard remote arterial blood gas analyser: A randomized controlled trial. (May 2022) - Mitchell, Kay; Salmon, Karen E; Egbosimba, David; Troughton, Gavin; Grocott, Mike PW
Introduction: The Proxima TM point of care (POC) device enables arterial blood gas (ABG) samples to be analysed without the nurse leaving the patient. The benefits of this for work efficiency have not been evaluated. Methods: We compared the time taken to obtain an ABG result using Proxima TM versus a standard ABG sampling system. Twenty patients were randomized to ABG sampling using Proxima TM, or a standard ABG system. Nurses were observed performing all ABG sampling episodes for a minimum of 24 hours and no more than 72 hours. Results: The mean time taken to obtain a result using Proxima TM was 4:56 (SD = 1:40) minutes compared to 6:31 (SD = 1:53) minutes for the standard ABG technique (p < 0.001). Mean time away from the patient's bedside was 3.07 (SD = 1:17) minutes using the standard system and 0 minutes using Proxima TM (p < 0.001). Conclusions: Reduced time for blood gas sampling and avoidance of time away from patients may have significant patient safety and resource management implications, but the clinical and financial significance were not evaluated.